Research on Protection Section Setting of Urban Rail Transit Signaling System - ZHANG Datao (Kongzhi Yu Xinxi Jishu)
In urban rail transit, signaling system needs to set up overlap reasonably so as to meet the requirements of high speed route terminal train approaching, precise train stopping, and also to ensure driving safety. In this paper, by analyzing operation efficiency and construction cost of subway, combined with specific operation scenarios, a principle of setting up overlap was studied and formulated. The contradiction among operation efficiency, safety and cost of subway is well balanced. Combined with the real situations in Guanzi Lin Station of Changsha metro line 4, the rationality of the overlap setting principle under different operation scenarios is verified and efficient operation and flexibility of the organization are achieved.